Community Engagement and Field Trials of Genetically Modified Insects and Animals - Neuhaus, Carolyn P. (The Hastings Center report, 2018)
New techniques for the genetic modification of organisms are creating new strategies for addressing persistent public health challenges. For example, the company Oxitec has conducted field trials internationally—and has attempted to conduct field trials in the United States—of a genetically modified mosquito that can be used to control dengue, Zika, and some other mosquito-borne diseases. In 2016, a report commissioned by the National Academies of Sciences, Engineering, and Medicine discussed the potential benefits and risks of another strategy, using gene drives. Driving a desired genotype through a population of wild animals or insects could lead to irreversible genetic modification of an entire species. The NASEM report recommends community, stakeholder, and public engagement about potential uses of the technology, and it argues that the engagement should occur as research advances, well before gene drives are deployed. Yet what “engagement” means in practice is unclear. This article seeks clarity on this problem by offering a justification for community engagement and drawing out implications of this argument for the implementation and desired outcomes of community engagement. Community engagement is essential when it comes to research that would release genetically modified insects or animals into the environment. By contrast, obtaining informed consent from people who live near such a proposed field trial is neither necessary nor sufficient. Drawing on the epistemic and moral arguments for deliberative democracy, I propose two discrete mechanisms of community engagement: community advisory boards and deliberative forums, neither of which has been systematically incorporated into research governance. The proposed mechanisms would engender respect for persons who live near field trials, even when the results of deliberation override some individuals’ preferences. Community engagement foregrounds the community in our thinking about humans’ relationship to nature, and it implies that deciding to release genetically modified insects or animals into the wild ought to be a collective decision, not one made by product developers, policy-makers, private companies, research funders, or scientists alone.